Formulation and verification of 3D in-situ stress estimation based on differential-direction drilling. (September 2021) - Lin, Cui; Zou, D.H. Steve
Abstract: A three-dimensional stress field underground has six independent components. They are among the key factors that affect ground stability. Estimation of the magnitudes and orientations of the 3D in-situ stresses is of practical importance in underground engineering projects. At present the only method that is capable of measuring the complete 3D stresses is the overcoring method, which is however expensive and cannot be applied to a deep well in petroleum engineering due to lack of access. This paper presents an alternative method for estimating the complete 3D stresses based on back-analysis of convergence measured in multiple boreholes. This method requires differential-direction drilling and measurements of diametrical borehole convergence in three non-parallel planes. It has also taken into consideration of the field conditions in petroleum engineering and analyzed the effects of pore pressure, mud pressure and permeability of the rock mass and well wall. Overall, a total of five mathematical models (one in linear elastic and four in poro-elastic) are developed for the anticipated field scenarios. For each model, comprehensive formulations correlating the measured convergence with the in-situ stresses are presented. Data compatibility in different directions of individual boreholes is achieved by proper coordinate transformation. The method has been verified using simulated data and the results match well the original input.